Analisis Pengaruh Digital Marketing dan Citra Merek terhadap Minat Beli pada Toko Kecantikan Sociolla - Priscilla Heline Suciadi; Jesslyn Angelika Lionard; Monalisa (Jurnal Online Manajemen ELPEI, 2026)
This study explores the comparative influence of digital marketing and brand image on purchase intention within Indonesia’s beauty e-commerce sector, taking Sociolla as the empirical setting. The research is motivated by growing uncertainty surrounding the behavioural effectiveness of digital marketing among digital-native consumers who increasingly experience advertising fatigue. A quantitative correlational approach was employed, and the data were analysed using a series of statistical procedures, including normality assessment, correlation testing and multiple regression, to evaluate the extent to which each predictor contributes to purchase intention. The findings reveal a clear imbalance in influence. Digital marketing does not demonstrate a significant effect on purchase intention, suggesting that promotional visibility alone is no longer sufficient to encourage behavioural responses. By contrast, brand image shows a strong and meaningful positive influence, highlighting the importance of credibility, authenticity and perceived product safety in shaping cosmetic purchasing decisions. The overall model displays a high explanatory ability, reinforcing the central role of brand-related trust cues in guiding consumer behaviour within high-risk product categories. The study contributes to existing theoretical perspectives by strengthening empirical support for the asymmetric influence model and extending signalling and trust–risk approaches to the context of Indonesian beauty e-commerce. In practical terms, the findings suggest that platforms should give greater emphasis to credibility-building strategies, including authenticity verification and transparent product information, rather than relying heavily on promotional volume. The study concludes that brand image is the dominant factor shaping purchase intention in online beauty product purchases.